Bond-slip Behaviour of NSM GFRP Bars in Reinforced Recycled-Aggregate Concrete: Experiments and a Modified Model - Anh-Tuan Le; Thuy Ninh Nguyen; Vui Van Cao (Salehan Institute of Higher Education, 2023)
Bond-slip behaviour of glass fiber-reinforced polymer (GFRP) bars embedded in conventional concrete has been widely investigated. In contrast, the bond-slip behaviour of near-surface mounted (NSM) GFRP bars bonded in reinforced recycled aggregate concrete (RAC) seems to be less explored, while recycled materials have been increasingly used due to reasons of environmental pollution and resource exhaustion. This study aimed to experimentally and theoretically examine the bond-slip behaviour of NSM GFRP bars in reinforced RAC under monotonic and cyclic loadings. To achieve this aim, twenty-four tests were performed, which were divided into two groups by monotonic and cyclic loadings. In each group, twelve tests were performed on ten reinforced RAC specimens and two reinforced normal aggregate concrete (NAC) specimens. The test results confirmed the brittle shear failure of concrete in the proximity of a resin-concrete surface. Bond-slip behaviour can be characterized by nonlinear and linear branches, in which the linear branch dominates the behaviour. Under monotonic and cyclic loadings, the average slips of GFRP bars in reinforced RAC were 0.238 and 0.284 mm, and their coefficients of variation (COV) were relatively large at 0.142 and 0.130, respectively. In contrast, ultimate loads had a relatively low COV of around 0.038. The effect of cyclic loading significantly increased the ultimate slip by 19.3%, whereas it negligibly reduced the ultimate load; consequently, the stiffness was reduced by 19.4%. A modified smooth model was proposed to predict the bond-slip behaviour of NSM GFRP bars in reinforced RAC under monotonic and cyclic loadings. The simplicity and accuracy of the model can be useful for engineers in structural retrofitting using NSM FRP technique. Doi: 10.28991/CEJ-2023-09-02-01 Full Text: PDF